Functional assessment and phenotypic heterogeneity of SFTPA1 and SFTPA2 mutations in interstitial lung diseases and lung cancer. Issue 6 (24th December 2020) - Legendre, Marie; Butt, Afifaa; Borie, Raphaël; Debray, Marie-Pierre; Bouvry, Diane; Filhol-Blin, Emilie; Desroziers, Tifenn; Nau, Valérie; Copin, Bruno; Dastot-Le Moal, Florence; Héry, Mélanie; Duquesnoy, Philippe; et al.
Introduction: Interstitial lung diseases (ILDs) can be caused by mutations in the SFTPA1 and SFTPA2 genes, which encode the surfactant protein (SP) complex SP-A. Only 11 SFTPA1 or SFTPA2 mutations have so far been reported worldwide, of which five have been functionally assessed. In the framework of ILD molecular diagnosis, we identified 14 independent patients with pathogenic SFTPA1 or SFTPA2 mutations. The present study aimed to functionally assess the 11 different mutations identified and to accurately describe the disease phenotype of the patients and their affected relatives. Methods: The consequences of the 11 SFTPA1 or SFTPA2 mutations were analysed both in vitro, by studying the production and secretion of the corresponding mutated proteins and ex vivo, by analysing SP-A expression in lung tissue samples. The associated disease phenotypes were documented. Results: For the 11 identified mutations, protein production was preserved but secretion was abolished. The expression pattern of lung SP-A available in six patients was altered and the family history reported ILD and/or lung adenocarcinoma in 13 out of 14 families (93%). Among the 28 SFTPA1 or SFTPA2 mutation carriers, the mean age at ILD onset was 45 years (range 0.6–65 years) and 48% underwent lung transplantation (mean age 51 years). Seven carriers were asymptomatic. Discussion: This study, which expands the molecular and clinical spectrum of SP-A disorders, shows that pathogenic SFTPA1 or SFTPA2 mutations share similar consequences for SP-A secretion in cell models and in lung tissue immunostaining, whereas they are associated with a highly variable phenotypic expression of disease, ranging from severe forms requiring lung transplantation to incomplete penetrance. SFTPA1 and SFTPA2 mutations lead to similar alterations in SP-A secretion and lung tissue expression. They are associated with a highly variable phenotypic expression ranging from incomplete penetrance to severe interstitial lung diseases and lung cancer. https://bit.ly/30SrEVb